Pemanfaatan Sampah Organik Rumah Tangga Menjadi Pupuk Organik Cair Sebagai Salah Satu Upaya Mengurangi Volume Sampah di RT 005 Kelurahan Kampung Baru Tahun 2021 - Veronika Amelia Simbolon; Mutia Diansafitri (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Household waste is often ignored and thrown away, so that it can have a bad impact on the environment, but waste can be utilized if it is managed such as animal feed or fertilizer. Fertilizers produced from organic materials contain nutrients needed by plants, use for a long time does not damage the soil and is environmentally friendly so it is safe to use on plants. The purpose of community service is to provide education to residents of RT 005 about the use of organic waste as organic fertilizer so that they can increase the knowledge and understanding of residents on how to reduce the volume of waste and use it as organic fertilizer. The implementation method consists of the preparation stage, activity plan, activity implementation stage, implementation method and activity relevance. The results of the activity, namely, the socialization participants were very enthusiastic about participating in the activity, especially after being given education through the provision of materials, video screenings and simulations of making liquid organic fertilizer. Residents can use the simulated fertilizer directly on plants in their yard. The participants gained knowledge about the use of household organic waste into fertilizer through community service activities. The focus of the activity is on managing household waste, so that the residents of RT 005 are able to independently manage waste. It is hoped that the government's active role in conducting intense education to the community as an effort to control waste starting from the source of the waste.